ANALISIS STATUS DAYA DUKUNG AIR DI SUB DAS CIKERUH MENGGUNAKAN METODE SOIL CONSERVATION CURVE NUMBER (SCS-CN) - Edy Suryadi; Dwi Rustam Kendarto; Kania Gita Pramadita (Jurnal Agritechno, 2021)
The Cikeruh sub-watershed is an area with a high population growth rate, which causes land conversion to occur in several sub-districts hence has implications for decreasing water availability and increasing water demand in the Cikeruh sub-watershed. This study aims to determine the status of water carrying capacity in the Cikeruh sub-watershed by comparing the ratio between water demand and availability. Water demand is calculated using the standard determined by SNI 19-66728.1, 2002; SNI 67281-2015; and the Directorate General of Human Settlements of the Public Works Service in 1996, while the sectors calculated are domestic, non-domestic, industrial, agriculture, animal husbandry, and fisheries. Water availability is calculated by estimating the volume of flow that occurs in the Cikeruh sub-watershed using the Soil Conservation Service Curve Number (SCS-CN) method from USDA involving hydrological data from 2011 to 2020. The result showed that the water availability in the Cikeruh sub-watershed in 2020 was 350,962,957.9 m3/year, while the water demand in the Cikeruh sub-watershed changes dynamically every year. The water demand in the Cikeruh sub-watershed in 2011 was 588,925,151 m3/year. In 2015, it was 754,796,534 m3/year, while in 2020 was 571,509,488 m3/year. The calculation results showed a water deficit in the Cikeruh sub-watershed, where the value of water demand is higher than the water availability, the ratio is 0.641, which means that the environmental carrying capacity has exceeded (overshoot) because the ratio value is < 1.